Strategi Perbankan Syariah dalam Meningkatkan Inklusi Keuangan dan Pengentasan Kemiskinan: Tinjauan Pustaka di Indonesia - Alamsa Alamsa; Olivia Pamilangan Andi’lolo; Iqrima Mas Mappangile (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the strategic role of Islamic banking in expanding financial inclusion and alleviating poverty in Indonesia. Using a qualitative literature review methodology, this research analyzes academic literature, regulations, and official reports to identify the contributions, challenges, and optimization strategies of Islamic banking. Findings indicate that Islamic banking provides financing alternatives aligned with Islamic values through products such as mudharabah, musyarakah, and murabahah, enabling low-income communities to access capital without interest burdens. The management of Islamic social funds including zakat, infaq, sadaqah, and waqf strengthens social capital for micro-enterprise empowerment. However, significant barriers exist, including low Islamic financial literacy, limited access in remote areas, and suboptimal regulations. This study recommends enhancing financial literacy, developing technology-based inclusive products, strengthening supportive regulations, and fostering multi-stakeholder collaboration to optimize the role of Islamic banking as an instrument for inclusive and equitable economic development in Indonesia. The research contributes to the theoretical understanding of Islamic banking's potential in addressing financial exclusion and poverty while providing practical insights for policymakers and banking institutions.